Esophageal Gastrointestinal Stromal Tumor: Diagnostic Complexity and Management Pitfalls. (30th April 2013) - Markakis, Charalampos G.; Spartalis, Eleftherios D.; Liarmakopoulos, Emmanouil; Kavoura, Evangelia G.; Tomos, Periklis
Abstract : Introduction . Gastrointestinal stromal tumors of the esophagus are rare. Case Presentation . This is a case of a 50-year-old male patient who was referred to our department complaining of atypical chest pain. A chest computed tomographic scan and endoscopic ultrasound revealed a submucosal esophageal tumor measuring 5 cm in its largest diameter. Suspecting a leiomyoma, we performed enucleation via right thoracotomy. The pathology report yielded a diagnosis of an esophageal gastrointestinal stromal tumor. The patient has shown no evidence of recurrence one year postoperatively. Conclusions . This report illustrates the complexity and dilemmas inherent in diagnosing and treating esophageal GISTs.